Letter - Schevenels, Walther, b. 1894
028-0051-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, AVENUE D'ORSAY, PARIS-VIIe EXECUTIVE COMMITTEE: President: W. M. Citrine, Great Britain. Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia General Secretary: W. Schevenels. Sch/H TELEGRAMS: INTERFED-PARIS TELEPHONE : INVALIDES 45-88 AFFILIATED COUNTRIES: Argentine Austria Belgium Canada Czechoslovakia Dantzig Denmark Dutch East Indies Estonia Finland France Great Britain Greece Holland Hungary India Luxemburg Memel Territory Mexico Norway Palestine Poland Roumania South Africa South-West Africa Spain Sweden Switzerland Yugoslavia 22nd February 1937. Mr. Walter M. Citrine, LONDON. Dear Comrade Citrine, I should like to inform you that, according to information now received from Valencia, the "Pelayo" and the "Carpio", which sailed on the 21st January from Liverpool and London, have arrived in Valencia. The International Solidarity Committee there decided that the two cargoes should be sent to Madrid, since the need is greater there than anywhere else, and the Union of Transport Workers undertook to unload the goods and transport them to Madrid. We now learn that forty lorries loaded with the consignment are already on their way to Madrid. Yours sincerely, W. Schevenels, General Secretary: 292/946/28/51